Duty to Serve: Sovereign Immunity in Municipal Water Utility Suits: Aligning Affordability with Public Health Goals in Rural Water Utility Systems - Yeluri, Sree (Columbia Journal of Environmental Law, 2026)
This Note examines the competing federal, state, and local interests in the regulation of drinking water utilities in rural areas. Focusing on the U.S. Department of Agriculture’s Water and Waste Disposal Loan and Grant Program (7 U.S.C. § 1926) as a case study, this Note explores legal challenges arising from the statute’s anti-curtailment provision. Suits under this provision are typically brought by state-created water utility districts against state public utility commissions and involve novel questions about the scope of municipal immunity and the likelihood of injunctive relief. These suits reveal a link between regulatory fragmentation and affordability. This Note then proposes two structural changes: first, state utility commissions must clarify that utilities’ public interest obligations include affordability; and second, state and federal agencies involved in regulating water utilities must prioritize regionalization to advance both safety and affordability. Strengthening public control over water utilities can help avoid Section 1926 litigation and facilitate increased access to affordable water for rural communities.